A distribuição dinâmica do ônus da prova em matéria tributária - Sartório Junior, Roberto (2019)
The purpose of this dissertation is to identify the applicability of the dynamic distribution of the burden of proof in tax lawsuits, especially regarding issues involving third party tax liability. This technique aims to seek the effectiveness of judicial protection with the scope of inhibiting the production of proof impossible by a party when the burden of proof falls on the adverse party that has better conditions to produce it. This will reflect, above all, on issues involving evidence of negative facts and assumptions. In this sense, to investigate the use of this technique, the paper will deal with the evaluation of evidence by the judge, in addition to the fundamental norms of the Code of Civil Procedure that support the use of dynamic distribution for the construction of truth in the process, given the contradictory and cooperation. Parallel to this, there will be an examination of the rules of presumption and of tax liability in order to demonstrate the need for the production of evidence by the Treasury to confirm the tax legal fact, besides highlighting the importance of the prior contradictory to support the redirection of tax execution. Therefore, it is verified that absent one of these factors, the dynamic distribution of the burden of proof should be applied in the tax process.